Scaffolding as a Bridge to Literature for Science and Engineering Students - Vungthong, Sompatu (Richtmann Publishing, 2012)
It has been held that science and literature stand at opposite poles. The fact that students at King Mongkutâ€™sUniversity Technology Thonburi (KMUTT), a university in Thailand which is known for science and engineering, have never hada chance to be exposed to literature through the English courses offered by the university seems to confirm this belief. Justrecently Reading Appreciation was offered as an elective course. The study then was conducted to investigate ways in which ateacher employs scaffolding techniques to help students, with no literature background and for some even with no interest,approach literary works critically. The study was framed by the Vygotskian concepts of scaffolding coined by the â€œzone ofproximal developmentâ€ that posits that children under adult guidance or in collaboration with more capable peers can developthemselves more successfully. Data in this study were derived from the recordings of the teacher-student interaction in ReadingAppreciation Course and the studentsâ€™ journals. The focus of this study consisted of 6 science and engineering students.Looking at a variety of types of scaffolds used in class based on cognitive and linguistic aspects, the study showed that throughscaffolding literature can be made appealing to science and engineering students and they can respond to literature critically.